Chicory R2R3-MYB transcription factors CiMYB5 and CiMYB3 regulate fructan 1-exohydrolase expression in response to abiotic stress and hormonal cues - Wei, Hongbin; Bausewein, Anja; Greiner, Steffen; Rausch, Thomas (The journal of experimental botany, 2017)
Chicory R2R3-MYB transcription factors CiMYB5 and CiMYB3 activate promoters of 1-FEH genes (1-FEH1, 1-FEH2a, and 1-FEH2b) and are co-expressed with their target
Gesehen am 30.04.2019